Anthocyanins in blue berries of Vaccinium padifolium - Cabrita, Luís (2011)
Twenty anthocyanins were isolated from the extract of the edible blue berries of Vaccinium padifolium (Uveira) by a combination of chromatographic techniques. Mainly on the basis of nuclear magnetic resonance techniques (1H, COSY, TOCSY, HSQC, HMBC, SEFT) they were identified as the 3-O-beta-glucopyranosides, 3-O-beta-galactopyranosides, 3-O-beta-arabinopyranosides and 3-O-sambubiosides (2'-O-beta-xylopyranosyl-O-beta-glucopyranosides) of delphinidin, cyanidin, petunidin,malvidin and peonidin. Anthocyanidin disaccharides have not been identified in the genus Vaccinium previously, and the 3-sambubiosides of peonidin, petunidin and malvidin are novel compounds.